2015
DOI: 10.1007/s00402-015-2156-3
|View full text |Cite
|
Sign up to set email alerts
|

Survey on the management of acute first-time anterior shoulder dislocation amongst Dutch public hospitals

Abstract: IntroductionThe primary aim of this study was to record how orthopaedic surgeons are currently managing acute first-time anterior shoulder dislocation (AFASD) 8 years after introduction of the Dutch national guideline: “acute primary shoulder dislocation, diagnostics and treatment” in 2005. The second aim was to evaluate how these surgeons treat recurrent instability after AFASD.Materials and methodsAn online questionnaire regarding the management of AFASD and recurrent shoulder instability was held amongst or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…Various open and arthroscopic techniques have been developed overtime to address the glenohumeral joint instability with the ultimate goal of restoring the shoulder function and lowering the rate of recurrent instability over the long-term. Bankart repair is currently the treatment of choice according to various surveys of surgeons, with > 90% of surgeons choosing the Bankart procedure as initial repair procedure [3,4,14]. A review of the American Board of Orthopaedic Surgery revealed a significant increase in the percentage of arthroscopicallyperformed Bankart repairs was noted, being performed in approximately 88% of cases between 2006 and 2008, compared to 71% in the period from 2003 to 2005 [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various open and arthroscopic techniques have been developed overtime to address the glenohumeral joint instability with the ultimate goal of restoring the shoulder function and lowering the rate of recurrent instability over the long-term. Bankart repair is currently the treatment of choice according to various surveys of surgeons, with > 90% of surgeons choosing the Bankart procedure as initial repair procedure [3,4,14]. A review of the American Board of Orthopaedic Surgery revealed a significant increase in the percentage of arthroscopicallyperformed Bankart repairs was noted, being performed in approximately 88% of cases between 2006 and 2008, compared to 71% in the period from 2003 to 2005 [35].…”
Section: Introductionmentioning
confidence: 99%
“…Methods: A total of 100 patients were primarily operated using arthroscopic Bankart repair after traumatic anterior shoulder instability. Medical records were retrospectively reviewed, and patients were assessed using postal questionnaire after a mean follow-up of 8.3 years [3][4][5][6][7][8][9][10][11][12][13][14]. Clinical assessment was performed using Constant score, Rowe score, and American Shoulder and Elbow Surgeons score.…”
mentioning
confidence: 99%
“…While the indications for operative intervention in young, active, males with first-time Fig. 7 a, b Clinical photographs of a patient wearing an external rotation immobilizer dislocations are expanding and becoming more common [66,67], there still remains a significant role for nonoperative treatment in older individuals, noncontact athletes, lower-demand populations, individuals who present with significant losses in range of motion, in-season athletes, patients with ligamentous laxity, and individuals who cannot tolerate general anesthesia. Physical therapy is critical to shoulder stability through the recruitment and maintenance of dynamic stabilizers and scapulothoracic musculature-subscapularis, supraspinatus, infraspinatus, teres minor, teres major, biceps brachii, trapezius, and deltoid muscles.…”
Section: Physical Therapymentioning
confidence: 99%
“…In patients with first-time traumatic anterior shoulder dislocation, if a fracture requiring rigid fixation, such as greater tuberosity fracture with displacement >5 mm 59) or glenoid fracture with bone loss >20% of the glenoid diameter [51][52][53][54] is not accompanied, the initial treatment should be focused on early closed reduction, immobilization, and physical therapy with the goal to restore motion and strength. Riccio et al 60) suggested effective rehabilitative approach as the conservative management in adults with first episode of traumatic anterior shoulder disloca-tion.…”
Section: Conservative Versus Surgical Treatmentmentioning
confidence: 99%